Pengaruh Kepemimpinan Kepala Sekolah, Lingkungan Kerja dan Motivasi Kerja Terhadap Kinerja Guru SMP Negeri di Kota Palembang - Hidayat, M. Sondy; Choiriyah, choriyah (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
This research aims to determine the influence of the principal's leadership, work environment and work motivation together on the performance of State Middle School teachers in the City of Palembang and the impact of the principal's leadership, work environment, and work motivation partially on the performance of State Middle School teachers in the City of Palembang. The data used in this research is primary data from the answers of 171 State Middle School teacher respondents in Palembang City. The analysis method used is Multiple Linear Regression and Validity and Reliability testing. Classic assumption testing is in the form of the Normality Test, Multicollinearity Test, and Heteroscedasticity Test. The research results show that the principal's leadership, work environment, and work motivation significantly influence the performance of State Middle School teachers in Palembang City. Partially, there is a significant influence of the principal's leadership and work environment on teacher performance, and there is no significant influence of work motivation on the performance of State Middle School teachers in Palembang City. The principal leadership variables, work environment, and work motivation increased teacher performance variables, amounting to 85.6%. Meanwhile, the remaining 14.4% is explained by other variables not included in this research, such as leadership style, pedagogical competence, organizational culture, and work morale